An Evaluation of the Utility of the Breast Reconstruction Risk Assessment Score Risk Model in Prepectoral Tissue Expander Breast Reconstruction. (May 2020) - Martin, Shanique; Turner, Elizabeth; Nguyen, Alan; Thornton, Brian; Nazerali, Rahim S.
Abstract : Introduction: Individualized postsurgical risk assessment models provide surgeons and patients with information that is vital to the surgical decision-making process. One such tool, the Breast Reconstruction Risk Assessment (BRA) score, uses a limited selection of patient-specific factors to predict 30-day postsurgical risk of surgical site infection, seroma, dehiscence, reoperation and explantation associated with immediate submuscular tissue expander breast reconstruction. This model's performance in prepectoral tissue expander reconstruction has not been previously reported. Here, we evaluate the performance of the BRA score model in a population of patients who underwent immediate prepectoral tissue expander breast reconstruction. Materials and Methods: A retrospective chart review was conducted of prepectoral breast reconstructions performed in 2 institutions between January 2017 and December 2018. Complications occurring within 30 days postoperatively were documented and compared with the BRA score predicted risk for each patient. Results: Overall 247 patients (average age, 49.2 years) were included in the study. The mean BRA score predicted 30-day risk of a complication was 13.0% (7.5–41.5%). The observed rate of 30-day postoperative complications was 31.2% (77 patients), though only 36 (14.6%) patients had complications included in the model. The remaining patients experienced skin necrosis or hematoma as their only early complication. The 30-day BRA score model demonstrated good fit for the overall occurrence of any of the BRA score predicted complications (Hosmer-Lemeshow 0.7167), though the model discrimination was poor (C statistic <0.60). Notably, half of the 30-day postsurgical complications observed in this study were due to skin necrosis, a complication not currently included in the 30-day BRA score model. Conclusions: Our results indicate that the current 30-day BRA score model may have poor predictive value in prepectoral breast reconstruction. The most common early complication observed, skin necrosis, is not currently included in the model, suggesting that caution should be applied when using this risk predictive calculator as an adjunct to patient evaluation and counseling. Abstract : Supplemental digital content is available in the text.